2016
DOI: 10.7904/2068-4738-vii(14)-89
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Cumulative Biogas Yield of Yellow Yam Brute Co–digested With Cow Paunch Manure in Batch Mode

Abstract: Abstract. Anaerobic digesters were used in a study to compare cumulative biogas yield from yellow yam brute, cow paunch and yellow yam brute co-digested with cow paunch manure. It was found out that the mixture slurry of yellow yam brute mixed with cow paunch (YYB+CP) had the highest cumulative biogas yield of 668.65 mL/TMS than the cumulative biogas yield of 587.86mL/TMS and 307.96 mL/TMS obtained from the single base line substrates of cow paunch and yellow yam brute, respectively within the 35 days hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Jackfruit recorded the lowest production of biogas (495 mL) while banana recorded the second lowest (555 mL)., however, these results are relatively higher compared to the current study. Umeghalu et al [54] observed an increase in gas yield from 343.56 to 610.2 mL when co-digested with cow paunch and from 314.6 to 550.66 mL when co-digested with poultry droppings within the same 30 days observation period. Generally, the hydraulic retention time for all the treatments was 30 days.…”
Section: Quantity Of Biogasmentioning
confidence: 97%
“…Jackfruit recorded the lowest production of biogas (495 mL) while banana recorded the second lowest (555 mL)., however, these results are relatively higher compared to the current study. Umeghalu et al [54] observed an increase in gas yield from 343.56 to 610.2 mL when co-digested with cow paunch and from 314.6 to 550.66 mL when co-digested with poultry droppings within the same 30 days observation period. Generally, the hydraulic retention time for all the treatments was 30 days.…”
Section: Quantity Of Biogasmentioning
confidence: 97%
“…According to Umeghalu, Okwonko, Ngini and Okoye (2015) and Pavithran et al (2015), jackfruit waste was codigested jackfruit with chicken droppings and cow dung to enhance biogas production. However, both studies disagreed on the pretreatment method used.…”
Section: Some Of the Earlier Studies Of Biogas Production From Jackfr...mentioning
confidence: 99%
“…The study by Pavithran et al (2015) pretreated jackfruit waste by reducing the substrate particle sizes and addition of tungsten as a catalyst and sodium hydrogen carbonate to control the pH. The study by Umeghalu et al (2015) also pretreated jackfruit waste by reducing the substrate particle sizes but after soaked it for 20 days before anaerobic digestion. Other researchers like (Amin et al, 2017) have proved that sodium hydroxide improves the digestibility of substrates and increase methane yield.…”
Section: Some Of the Earlier Studies Of Biogas Production From Jackfr...mentioning
confidence: 99%
See 2 more Smart Citations